2003
DOI: 10.1098/rstb.2002.1219
|View full text |Cite
|
Sign up to set email alerts
|

Imitation as behaviour parsing

Abstract: Non-human great apes appear to be able to acquire elaborate skills partly by imitation, raising the possibility of the transfer of skill by imitation in animals that have only rudimentary mentalizing capacities: in contrast to the frequent assumption that imitation depends on prior understanding of others' intentions. Attempts to understand the apes' behaviour have led to the development of a purely mechanistic model of imitation, the 'behaviour parsing' model, in which the statistical regularities that are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 63 publications
(68 reference statements)
1
117
3
2
Order By: Relevance
“…In associative sequence learning, this generality is programmatically wide, with the risk of losing sight of human-specific imitation capabilities. Byrne (2003Byrne ( , 2005 has made a strong case for imitation as a special faculty. He suggests that the capacity for imitation learning, requiring powerful cognitive processes of de-and re-composing complex behaviour, might have co-evolved with the perceptual decomposition power of the mirror neuron system that had originally evolved in response to social needs, namely action understanding (Byrne, 2005; see also Arbib, 2005;Lyons, Santos, & Keil, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In associative sequence learning, this generality is programmatically wide, with the risk of losing sight of human-specific imitation capabilities. Byrne (2003Byrne ( , 2005 has made a strong case for imitation as a special faculty. He suggests that the capacity for imitation learning, requiring powerful cognitive processes of de-and re-composing complex behaviour, might have co-evolved with the perceptual decomposition power of the mirror neuron system that had originally evolved in response to social needs, namely action understanding (Byrne, 2005; see also Arbib, 2005;Lyons, Santos, & Keil, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Distinctions between different forms or 68 ‗mechanisms' of social learning are ultimately based on distinctions between the precise 69 means by which one individual ‗copies' aspects of another individual's behavior (Whiten et 70 al., 2009b). One distinct form of social learning is ‗imitation' (Thorndike,1898), which is 71 differentiated from other forms of social learning mechanisms because the social learner 72 copies the precise details and sequences of behavioral actions employed by a ‗model' (Heyes,73 1993; Byrne, 2003;Tomasello et al, 1993). Hence, a straightforward operational definition of 74 imitation (see e.g., Whiten et al, 2009b) states simply that it is the copying of demonstrated 75 behavior(s) exhibited by a model (e.g., the actions involved in the production of an artifact).…”
Section: Introduction 25mentioning
confidence: 99%
“…Measurement invariance is, therefore, considered a crucial step in cross-cultural research, as instruments can vary in their measurement qualities and validity across cultures. Configural invariance may even hold while measurement is non-invariant across groups (Byrne, 2003). Byrne (2003) points to bias as one of the primary concerns in crosscultural research.…”
Section: Overviewmentioning
confidence: 99%
“…Configural invariance may even hold while measurement is non-invariant across groups (Byrne, 2003). Byrne (2003) points to bias as one of the primary concerns in crosscultural research. In particular, construct-, instrument-, and item-derived bias are not uncommon concerns in cross cultural research (Byrne, 2003) and these biases can result in measurement non-invariance.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation